Method and system for task scheduling based on cloud manufacturing - YANG SHANLIN; LU XIAONONG; PENG ZHANGLIN; ZHAO SHUANGYAO; ZHANG QIANG; ZHANG XU; WANG WANYING (2017)
The invention discloses a method and a system for task scheduling based on cloud manufacturing. The method for task scheduling based on cloud manufacturing comprises: obtaining a to-be-executed task set of current time, and demand resources of each task in the task set; when the demand resource does not exist in a resource library, converting a task flow corresponding to the demand resource to a to-be-executed task set of next moment; when the resource library has the demand resource, according to one of index parameters, performing first layer grading on the task, if a plurality of tasks exist in a same grade, transferring the tasks to a next layer and continuing to perform grading according to another scheduling index, and executing the tasks in sequence from high grade to low grade, until all tasks are executed. The task scheduling method eliminates conflicts occur in a task scheduling process using a layer-by-layer grading method, and task scheduling efficiency is improved. 本发明公开种基于云制造的任务调度方法及系统。所述任务调度方法包